Pediatric Mycoplasma pneumoniae-induced rash and mucositis in China: clinical spectrum, co-infections and risk factors for recurrence—a retrospective cohort study - Wang, Yang; Jiao, Lei; Ma, Lin; Xu, Zigang; Liang, Yuan (Frontiers in Allergy, 2025)
BackgroundMycoplasma pneumoniae–induced rash and mucositis (MIRM) is a unique entity distinct from both erythema multiforme and Stevens-Johnson syndrome/toxic epidermal necrolysis. There are limited data on pediatric cases of MIRM in China.ObjectiveTo evaluate the clinical characteristics and recurrence frequency of pediatric cases of MIRM and to summarize the co-infections beyond M. pneumoniae infection.MethodsThis retrospective study was conducted through a chart review of patients with MIRM admitted to dermatology inpatient department from September 2017 to July 2021. Pediatric patients with MIRM 4 years to 12 years who met Canavan's criteria were included in the study.ResultsA total of 23 patients with MIRM aged 7.86 ± 2.92 years were included. Oral mucosa was the most common site of mucosal involvement. Average number of involved mucous membranes was 2.83 ± 0.89. Average length of hospital stay was 10.30 ± 3.34 days. Length of hospital stay in recurrent cases was shorter than isolated cases (6.3 days vs. 10.17 days). Recurrence was observed in 21.7% of patients. The number of mucosal membranes involved was more in the first episode of recurrent cases than isolated cases (3.2 vs. 2.72). Of all patients, 47.8% were co-infected with pathogens apart from M. pneumoniae. Recurrence rate of the co-infection group was 36.4%.ConclusionWe report observations from the largest pediatric cohort with MIRM in China. Patients with younger age at onset had more severe skin and mucosal involvement, even similar to SJS/TEN. A higher recurrence rate and incidence of co-infections were observed in our cohort. The co-infection group had a higher recurrence rate, which further supports the concept of reactive infectious mucocutaneous eruption.